Erratum: Publisher Correction: Shared heritability and functional enrichment across six solid cancers (Nature communications (2019) 10 1 (431)) - Jiang, Xia; Finucane, Hilary K.; Schumacher, Fredrick R.; Schmit, Stephanie L.; Tyrer, Jonathan P.; Han, Younghun; Michailidou, Kyriaki; Lesseur, Corina; Kuchenbaecker, Karoline B.; Dennis, Joe; Conti, David V.; Casey, Graham; et al. (Nature Communications, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2019-10-01